Comparative Physiological and Transcriptome Analyses Reveal the Responses to Ocean Acidification Challenge of Mactra veneriformis with Different Shell Colors - Limei Chen; Gengyin Huang; Shuang Liang; Jian Liang; Hefeng Wang; Huiru Liu; Xiaoyu Wang; Li Li; Yongjun Guo; Wenguang Liu (Fishes)
Mactra veneriformis is highly susceptible to ocean acidification (OA) due to its low shell hardness during its rapid growth period. In this study, oxygen consumption rate, ammonia excretion rate, and transcriptome sequencing of mantle tissue analyses were conducted in white and purple shell-color populations of M. veneriformis under OA stress (pH = 7.6). The findings indicated a significant rise in oxygen consumption rates and ammonia excretion rates following acidification in both the two shell colors, while the clams with purple color showed comparatively lower basal metabolic levels. Transcriptomic analyses demonstrated the expression of key genes related to fatty acid synthesis were significantly inhibited, whereas genes involved in calcification, osmoregulation, and immune response were upregulated under OA exposure in the two shell-color groups. However, some genes such as CA and HSP showed a population-specific response between the two shell-color populations. KEGG enrichment analysis revealed that the MAPK signaling pathway and protein processing in the endoplasmic reticulum were significantly enriched in the two acidification groups. This study provides valuable insights into the response of M. veneriformis to OA stress and also helps to predict the future breeding of valuable strains of M. veneriformis.